Upaya Pencegahan Praktik Bank Emok Melalui Edukasi Literasi Perbankan, Kesadaran Hukum, dan Nilai-Nilai Islam sebagai Upaya Pencegahan Praktik Bank Emok di Kampung Warung Gede Desa Cibiru Wetan - Setiawati, Liya; Linda Novianti; Rahmadika, Sarah (Jurnal Abdimas Dedikasi Kesatuan, 2026)
Illegal lending practices known as bank emok remain prevalent in rural communities and generate adverse economic, social, and legal consequences. Limited financial literacy, low awareness of banking regulations, and insufficient knowledge of Islamic financial alternatives contribute to the community’s dependence on such practices. This community service program aims to enhance public understanding of banking literacy, legal awareness, and Islamic values as preventive measures against bank emok practices in Kampung Warung Gede, Cibiru Wetan Village, Bandung Regency. The program was implemented through educational socialization, interactive discussions, case-based explanations, and the distribution of simple educational materials. The results indicate an improvement in participants’ awareness of the risks associated with illegal lending, banking legal aspects, and the importance of choosing licensed and Sharia-compliant financial institutions. This program is expected to encourage more prudent, ethical, and sustainable financial behavior within the community.   Keywords: bank emok; financial literacy; Islamic finance; banking law; community service.